Pengaruh Sistem Informasi Akuntansi dan Digital Marketing terhadap Kinerja Keuangan UMKM di Eks Karesidenan Surakarta - Frido Oktaviandre; Nurita Elfani Prasetyaningrum; Ramadhian Agus Triono Sudalyo (Fakultas Teknik Universitas Hamzanwadi, 2026)
This study aims to analyze the influence of Accounting Information Systems (AIS) and Digital Marketing on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) in the Eks Karesidenan Surakarta region. The study employs a causal associative quantitative approach using a Likert-scale questionnaire distributed to 395 MSME respondents selected through Proportionate Stratified Random Sampling. Data analysis utilizes multiple linear regression. The results indicate that: (1) AIS has a positive and significant effect on MSME Financial Performance (t=5.803; Sig.=0.000); (2) Digital Marketing has a positive and significant effect (t=5.691; Sig.=0.000); and (3) simultaneously both variables have a positive and significant effect (F=47.382; Sig.=0.000) with an Adjusted R² of 52.4%.